A label-free strategy for visual genotyping based on phosphate induced coloration reaction. Issue 34 (10th August 2022) - Zhang, Jiaxing; Hui, Hui; Xu, Wei; Hua, Kai; Cui, Yali; Liu, Xiaonan
Abstract : Phosphate induced coloration reaction facilitates visual genotyping and the target variant can be accurately identified within 30 min from blood directly. Abstract : Genetic variation plays a crucial role in disease occurrence and development. However, current genotyping strategies not only require a long turnaround time for DNA purification, but also depend on sophisticated apparatus and complex data interpretation, which seriously limits their application in point of care diagnostic test scenarios. In this study, by integrating phosphate induced coloration reaction and loop-mediated isothermal amplification, a rapid and portable strategy for straightforward genotyping has been established to cater to the demand of precision medicine. By employing phosphate ions produced during the amplification as a signal generator, not only can the genotyping result be interpreted with only naked eye from a low-cost label-free strip, but also the amplification efficiency is increased to facilitate genotyping with a robust biological specimen ignoring DNA polymerase inhibitors. Moreover, the introduction of alkaline lysis for DNA release allows whole blood to be identified accurately avoiding DNA purification. As a proof of concept, the insertion/deletion polymorphisms of the angiotensin-converting enzyme, a crucial factor associated with cardiovascular and cerebrovascular diseases, has been selected as a model to evaluate the performance of this method. Accurate results can be obtained from as low as 1 ng genomic DNA within 30 min. For clinical specimen detection, a concordance rate up to 100% has been found compared with PCR-based electrophoresis. Thus, this novel strategy may serve as a promising tool for straightforward genotyping to provide timely diagnostic information, especially in resource-poor medical institutions.